Synthesis, structure, properties and applications of MXenes: Current status and perspectives - Ronchi, Rodrigo Mantovani; Arantes, Jeverson Teodoro; Santos, Sydney Ferreira (Ceramics international, 2019)
Researches on new 2D materials have been intensively performed over the years, strongly motivated by graphene's outstanding properties. One of the most promising classes of 2D materials under investigation is the MXenes, which are compounds obtained through chemical delamination of ternary (or quaternary) layered carbides or nitrides. MXene family possesses unique properties derived from their complex bonding (a mixture of metallic and covalent bonds) and electronic structures, atomic stacking, synthesis routes and surface terminal groups. Despite the growing interest in these materials, there is a lack of systematic information on MXenes. This manuscript aimed to review and comment the most relevant fundamental and technological aspects of MXenes, ranging from structural and electronic characteristics of these compounds, their relevant properties and potential applications and devices. The main properties and features described in the following sections, assessed by both experimental and theoretical approaches, allow a critical analysis of the current status, trends, and potentialities of MXenes, such as their use in energy related applications, electronic and photonic devices, reinforcements of composites, and biomedical applications. [Display omitted]